A new Early Paleogene fossil mammal locality in the central-eastern Nemegt Basin, Gobi Desert, Mongolia, and notes on mammalian biostratigraphy. (January 2023) - Yo, Khand; Hoffman, Eva A.; O'Leary, Maureen A.; Novacek, Michael J.
Abstract: We report new, fossiliferous Paleogene Naran Bulak Formation localities from the central-eastern part of the Nemegt Basin of the Gobi Desert, Mongolia. Early Paleogene localities have been identified previously only in the western half of the Nemegt Basin. The new localities, near the town of Daus, are also noteworthy for their geographical proximity to Ukhaa Tolgod, a Late Cretaceous Djadokhta Formation locality known for its numerous dinosaur, mammal, and lizard fossils. The Daus section consists of the Zhigden, Naran, and Bumban members of the Naran Bulak Formation at three localities, and mammal and ostracode fossils were discovered in the Naran Member. Noteworthy discoveries are a dentary of the pantodont Archaeolambda cf. A . planicanina, postcrania of Pantolambdodon, a skull of the gliroid Gomphos, and a partial skull with a worn and damaged dentition provisionally identified as an arctostylopid. Biostratigraphy has been the primary means of dating Paleogene Asian faunas, however, the local fauna from the new localities does not fit easily with established patterns. The Naran Member and Archaeolambda planicanina and the arctostylopid Palaeostylops typically have been allied with the Gashatan Asian Land Mammal Age (ALMA) and attributed to the latest Paleocene. By contrast, Gomphos repeatedly has been found in the Bumban Member and assigned a Bumbanian ALMA, which has been considered as the earliest Eocene. Pantolambdodon has been reported from middle Eocene Arshatan and Irdinmanhan ALMA beds. The co-occurrence of these taxa in Naran Member beds complicates the temporal interpretation of the new localities and the reliability of broader biostratigraphic patterns.